INDONESIAN LEGAL POLITICAL POLICIES ON IMMIGRATED CRIMINAL ACTION IN THE ERADICATION AND PREVENTION OF PERSONAL TRADE ACT: NORMATIVE –EMPIRIC AXIOLOGY - Muhammad Azzam Alfarizi (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Transnational crime has great potential in Indonesia, which is a developing country. Transnational crime is not only driven by free trade factors or weak law enforcement in Indonesia, but also by Indonesia's geographical area itself. In the midst of the nation's problems that are happening today are very much and require serious attention, one of the things that is of serious concern is People smuggling or human smuggling. This research is a normative legal research used in an effort to analyze legal materials by referring to legal norms set forth in statutory regulations. The results of the research show about how the criminal act of human smuggling is regulated in positive law in Indonesia and how the criminal responsibility for those who commit human smuggling crimes. From the research results, it can be concluded that the international community, including Indonesia, views people smuggling as a transnational organized crime that can threaten state security. The crime of human smuggling is regulated in the Immigration Law Number 6 of 2011. Criminal Liability for the Crime of People Smuggling is in accordance with Law Number 6 of 2011 Article 120.